2015
DOI: 10.1016/j.drugalcdep.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Stress and alcohol use in rural Chinese residents: A moderated mediation model examining the roles of resilience and negative emotions

Abstract: Objective Little research has been done on alcohol use and dependence among rural residents in China, a sub-population that might be under increased stress due to the rapid modernization and urbanization processes. We aimed to assess rural residents’ levels of stress, negative emotions, resilience, alcohol use/dependence and the complex relationships among them. Methods Survey data from a large random sample (n = 1145, mean age = 35.9, SD = 7.7, 50.7% male) of rural residents in Wuhan, China were collected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
(66 reference statements)
1
17
0
1
Order By: Relevance
“…It is considered to be an important step as studies found that negative emotions including stress and anxiety play a key role in drug dependence. 25 , 26 Both intervention and control groups demonstrated highest scores on harm reduction self-efficacy in social pressure conditions; however, social network characteristics such as family member using injections, using injections with the sexual partner have been associated with unsafe injection behaviors. 27 Regarding withdrawal condition, there may be other factors related to the improvement of self-efficacy including participants’ past experiences with withdrawal.…”
Section: Discussionmentioning
confidence: 96%
“…It is considered to be an important step as studies found that negative emotions including stress and anxiety play a key role in drug dependence. 25 , 26 Both intervention and control groups demonstrated highest scores on harm reduction self-efficacy in social pressure conditions; however, social network characteristics such as family member using injections, using injections with the sexual partner have been associated with unsafe injection behaviors. 27 Regarding withdrawal condition, there may be other factors related to the improvement of self-efficacy including participants’ past experiences with withdrawal.…”
Section: Discussionmentioning
confidence: 96%
“…Alcohol consumption can often be considered a coping strategy for stressful life events 29 , especially in people with changes in their mental health such as anxiety, depression and self-esteem 30 . In this context, resilience is an important feature to moderate the association between stress and negative emotions by providing the individual with the ability to adapt to stressful circumstances while maintaining their mental well-being 31 . It should be noted that few studies have been developed to directly verify the relationship between alcohol consumption/dependence and resilience, especially in the older adult population, but those found in the literature indicate an inverse relationship between these two variables, since resilience has been identified as a protective mechanism associated with a reduced risk of consuming alcoholic beverages 31 - 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is perceived that stressful events are inevitable in life, however the “resilience” characteristic is key for explaining individual differences in psychological and behavioral improvement in confronting these events 31 . Thus, establishing a relationship between changes in self-esteem and negative events in life with alcohol consumption/dependence becomes clear, while resilience appears as a protective mechanism for these events that affect mental health and mitigate the impact of negative emotions, and thus reduce the consumption of alcoholic beverages 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence directly supporting the role of poor mental health in mediating the relationship between stress and risky sex and other health risk behaviours among various populations has been reported in the literature (Barbosa-Leiker et al, 2014; Wang and Chen, 2015). In a recent study among rural-to-urban migrants in China, a significant effect was observed for poor mental health status in mediating the association between migration-related stress and engagement in sex with high-risk partners (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 96%